PENINGKATAN KUALITAS PENDIDIKAN MELALUI PROGRAM BIMBINGAN BELAJAR DI UPT SDN 044 SIMANGULAMPE HUMBANG HASUNDUTAN - Eka Margareta Sinaga; Darinda Sofia Tanjung; Nova Florentina Ambarwati (PUAN INDONESIA, 2026)
This literacy and numeracy tutoring program is based on initial observations that found many students, both in lower and higher grades, still struggle with basic reading, writing, and arithmetic skills. To address this issue, students were grouped according to their respective weaknesses in difficult school subjects, with special groups for learning to read or count. The aim was to make students feel comfortable and at ease so that they could participate well in learning activities. The result was a very high level of student participation. Students also showed significant improvement in basic skills (reading, writing, and arithmetic) after being grouped according to their needs and weaknesses in the subject matter (reading/writing/arithmetic).